Intensitas Konsumsi Junk Food Pada Ibu Rumah Tangga Di Pedesaan Kabupaten Grobogan - Sudrajat, Agus (Universitas Ivet, 2025)
The lifestyle and dietary habits of Indonesians have undergone substantial changes, even in rural regions such as Grobogan Regency. Housewives play a crucial role in selecting and preparing meals for their families, making it essential to understand junk food consumption patterns in this demographic for improving nutritional status and preventing non-communicable diseases. This study aims to assess the correlation between junk food intake and nutritional status among housewives in rural settings. It employed an analytical observational approach with a cross-sectional design, conducted from January to February 2025. A total of 44 participants were selected using purposive sampling. Junk food consumption data were collected through the Food Frequency Questionnaire (FFQ). Bivariate analysis using gamma correlation was applied to examine the relationship between the variables with a significance level of p < 0.05. The analysis indicated no statistically significant association between junk food consumption and nutritional status (p = 0.972, p > 0.05), with a very weak correlation coefficient of 0.009. The absence of a relationship may be influenced by factors such as the frequency of consumption and physical activity levels.